2012
DOI: 10.1063/1.3681365
|View full text |Cite
|
Sign up to set email alerts
|

Standoff detection via single-beam spectral notch filtered pulses

Abstract: We demonstrate single-beam coherent anti-Stokes Raman spectroscopy (CARS), for detecting and identifying traces of solids, including minute amounts of explosives, from a standoff distance (>50 m) using intense femtosecond pulses. Until now, single-beam CARS methods relied on pulse-shapers in order to obtain vibrational spectra. Here we present a simple and easy-to-implement detection scheme, using a commercially available notch filter, that does not require the use of a pulse-shaper.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Previously, coherent anti-Stokes Raman scattering, was used for standoff detection [4], and recently detected small quantities at 50 meters with a 6 inch optic [5]. With a similar solid angle of collection, SB-SRS can detect four orders of magnitude less material in two orders of magnitude less time.…”
Section: Resultsmentioning
confidence: 98%
“…Previously, coherent anti-Stokes Raman scattering, was used for standoff detection [4], and recently detected small quantities at 50 meters with a 6 inch optic [5]. With a similar solid angle of collection, SB-SRS can detect four orders of magnitude less material in two orders of magnitude less time.…”
Section: Resultsmentioning
confidence: 98%
“…Several studies have investigated using nonlinear Raman methods such as coherent anti‐Stokes Raman spectroscopy (CARS) for standoff explosives detection . CARS is a nonlinear technique that traditionally utilizes two laser beams to excite a sample.…”
Section: Standoff Explosive Detectionmentioning
confidence: 99%
“…Bremer et al recently constructed a single‐beam CARS raster‐scan imaging spectrometer that was used to measure multispectral images of DNT at µg/cm 2 concentrations at 1 m . Natan et al developed a single‐beam CARS spectrometer that could measure analytes such as nitrate, urea, and RDX from 12 to 50 m away using a 19 cm lens . The authors demonstrated that RDX could be detected at 24 m with a 3 s accumulation time.…”
Section: Standoff Explosive Detectionmentioning
confidence: 99%
“…Thus the technique can be applied to media with strong multiple scattering. Let us note here that a similar technique has been suggested by using spectral-notch-filtered pulses in CARS demonstrated in [13], which allows researchers to obtain a signal with a signal-shaped pulse. Because of the behavior of the hole-filling signal with respect to one-and two-photon detuning, the technique has higher tolerance to background molecules and has the potential to detect a relatively small fraction of molecules among a vast amount of background.…”
mentioning
confidence: 91%